FAKTOR-FAKTOR DALAM PENGAMBILAN KEPUTUSAN LINDUNG NILAI (HEDGING) PADA INSTRUMEN DERIVATIF VALUTA ASING PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Elita W. R. Br Aritonang; Sylvia Christina Daat; Hastutie Noor Andrianti (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2018)
The transactions risk of international trading is occur by the risk of fluctuations in the foreign exchange rates. This unexpected changes in the value of foreign currency can have a significant impact on the companies, therefore companies need to perform risk managements which one of them is by performing hedging derivatives. The main purpose of this research is to test and prove empirically an issue related to the influence of Growth Oppotunity, Leverage, Firm size, LiquidityCash Ratio and Current Ratio to the probability of hedging decision making activity. The population in this study is a group of companies that listed on the Indonesia Stock Exchange (BEI) between period of 2011 and 2015. The sample in this study was attained by conducting a purposive sampling method with approximatelly 33 companies were obtained and used as sample for this research. While, several variables that used in this study including Growth Opportunity, Leverage,Firm Size, Likuidity Cash Ratio and Current Ratio. A logistic regresion analysis was used as an analytical tool in this research. Based on the results of logistic regression analysis shows that the Variable of Growth Opportunity, Leverage, Current Ratio have negatively affected the probability of decision making in hedging. While the variable of Firm Size and Cash Ratio have positively affected the probability of decision making in hedging